Pengaruh Pertumbuhan Ekonomi, Tingkat Inflasi, dan Upah Minimum Terhadap Jumlah Pengangguran Di Bali - Sopianti, Ni Komang; Ayuningsasi, A.A Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 4, April 2013 (pp. 173-225), 2013)
Unemployment is a problem that has yet to be addressed by the central government and local government. Various ways to overcome this problem has been taken by the government, but this problem has not been able to be resolved. Unemployment arises because of the mismatch between labor demand and labor supply. The unemployment problem is very important to note because it is equally harmful unemployment lead to a variety of crimes and can lead to social unrest, political, and poverty. As a trusted affect unemployment include economic growth, inflation rate, and the minimum wage. This study aimed to determine the effect of simultaneous or partial Which influential and dominant variables of economic growth, inflation rate, and the minimum wage for the number of unemployed in Bali. This study uses time series data for seven years that the year 2004-2010 and a cross section of nine Kabupaten/Kota in Bali. Analysis techniques are used to address the problem is with the multiple linear regression analysis model by performing the F test and t test. Results of this study showed that the variables of economic growth, inflation rate, and the minimum wage simultaneously significant effect on the number of unemployed in Bali. Variable inflation rates have a positive effect and significant on the number of unemployed in Bali, while the economic growth and the minimum wage has no effect on the number of partial unemployment in Bali. Dominant variable in this study is the rate of inflation, which positively affects the 26 percent unemployment rate in Bali. Variations influence of three independent variables can be determined based on the value of R2 is worth 0,308. Thus, 30.8 percent of variation in the number of unemployed is affected by economic growth, inflation rate, and the minimum wage, while the remaining 69.9 percent is influenced by other factors not included in the model such as population growth, health, education, geography, type of sex, and urbanization. Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4
Keywords: Unemployment , Economic Growth , Inflation , Minimum Wage